Fractures and Osteomalacia in a Patient Treated With Frequent Home Hemodialysis - Hanudel, Mark R. (Am J Kidney Dis, 2017)
Bone deformities and fractures are common consequences of renal osteodystrophy in the dialysis population. Persistent hypophosphatemia may be observed with more frequent home hemodialysis regimens, but the specific effects on the skeleton are unknown. We present an end-stage renal disease patient treated with frequent home hemodialysis who developed severe bone pain and multiple fractures, including a hip fracture and a tibia-fibula fracture complicated by non-union, rendering her non-ambulatory and wheelchair-bound for over a year. A bone biopsy revealed severe osteomalacia, likely secondary to chronic hypophosphatemia and hypocalcemia. Treatment changes included addition of phosphate to the dialysate, a higher dialysate calcium concentration, and increased calcitriol dose. Several months later, the patient no longer required a wheelchair and was able to ambulate without pain. Repeat bone biopsy revealed marked improvements in bone mineralization and turnover parameters. Also, with increased dialysate phosphate and calcium, as well as increased calcitriol, circulating FGF23 levels increased.